Effects of dietary supplementation with olive cake enriched in polyphenols on growth, rumen fermentation, and metabolic status of finishing Limousine bulls - V. Lopreiato; G. Ferronato; A. Amato; C. Cavallo; E. Trevisi; L. Llobat; V. Chiofalo; L. Liotta (Italian Journal of Animal Science)
This study aimed to evaluate the effects of supplementing olive cake (OC) enriched with polyphenols (EOC) on the performance, inflammometabolic response, and rumen metabolism of Limousine bulls. Thirty bulls were blocked by body weight (BW) and randomly allocated to two groups (15 per group): a 0% inclusion group (CTR) and a 13% inclusion group of EOC in the concentrate (EOC) for 80 days. At 0, 40, and 80 days of treatment, individual BW measurements and blood samples were collected, while rumen fluid samples were taken after slaughter. The EOC group exhibited higher levels of rumen propionate and heptanoate, along with lower levels of acetate, isobutyrate, and isovalerate compared to the CTR group. Additionally, the EOC group showed increased blood urea, γ-glutamyl transferase, and alkaline phosphatase, while levels of fructosamine, albumin, ferric reducing antioxidant power, calcium, and zinc were lower compared to the CTR group. Although performance did not differ significantly between the groups, the inclusion of OC in the concentrate may negatively impact feed efficiency, potentially leading to reduced liver functionality due to the high content of low-degradable NDF and elevated ADF levels in the enriched OC, along with possibly increased organic peroxides. Nonetheless, rumen fermentation data indicate a positive modulation of rumen metabolism towards volatile fatty acid (VFA) production pathways that reduce hydrogen ion availability for methane production.